2008
DOI: 10.1175/2007jamc1745.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Aerosols on the Summer Rainfall Frequency in China

Abstract: The authors investigate the short-term relationship between aerosol concentrations and summer rainfall frequency in China using the daily surface observations of particulate matters with a diameter of less than 10 m (PM10) mass concentration, rainfall, and satellite-observed cloud properties. Results in this study reveal that on the time scale of a few days aerosol concentration is positively correlated with the frequency of moderate-rainfall (10-20 mm day Ϫ1 ) days but is negatively correlated with the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 37 publications
0
30
1
1
Order By: Relevance
“…This trend for light rain is different from that of total rainfall observed in eastern China, which shows decreases in northern China and increases in southeastern China. Choi et al (2008) also showed that, over recent decades, increases in aerosol concentrations correlated negatively with the trend in light rain (< 5 mm d −1 ) and positively with changes in moderate rainfall (10-20 mm d −1 ) in China. A study by Rosenfeld et al (2008) proposed that interactions of aerosols with deep convective clouds could increase precipitation, which might be responsible for the observed increases in precipitation in southern China where aerosol concentrations were high and water vapor supply was adequate.…”
Section: Changes In Precipitation and Cloudsmentioning
confidence: 87%
“…This trend for light rain is different from that of total rainfall observed in eastern China, which shows decreases in northern China and increases in southeastern China. Choi et al (2008) also showed that, over recent decades, increases in aerosol concentrations correlated negatively with the trend in light rain (< 5 mm d −1 ) and positively with changes in moderate rainfall (10-20 mm d −1 ) in China. A study by Rosenfeld et al (2008) proposed that interactions of aerosols with deep convective clouds could increase precipitation, which might be responsible for the observed increases in precipitation in southern China where aerosol concentrations were high and water vapor supply was adequate.…”
Section: Changes In Precipitation and Cloudsmentioning
confidence: 87%
“…This finding can serve to resolve many contradictions related to interactions between aerosols, clouds, and precipitation. For example, an increase in precipitation caused by an increase in aerosol concentrations is particularly dominant over China (29) and the Amazon region (19), whereas the opposite is true over other regions; the former process is known as the so-called "cold rain process by IN particles," whereas the latter is known as the "warm rain process by cloud condensation nuclei particles." In this respect, the observed regional distribution of SCF shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PM 10 is easier to act as CCN and can impact low warm cloud. The enhancement of low-level warm cloud caused by lower PM 10 enriches warm-rain efficiency Choi et al, 2008b) and moderate rain is negligible, while the weak correlation coefficient shows that AOD and moderate rain have some relations. These results show very weak correlations between surface aerosols (e.g., PM 10 ) and moderate rain.…”
Section: Relation Between Precipitation and Aerosolmentioning
confidence: 95%